Addressing Healthcare Inequities in Disease Prevention Programs: Collaborative Roles of Nurses, Social Workers, and Epidemiology Inspectors - Wafi Mohammed Ahmed Al-Obaid; Zahraa Ali Abdullah Alnajem; Yasser Suliman Albuity; Ahmed Salman Alsohobi; Mohammad Sami Alhendas; Hussain Ali Rasasi; May Abdullah Alsalman; Bilal Jaber Aljafar; Mahdi Ahmad Alhamad; Abdulmohsen Abdullah Alabdulaziz (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare inequities remain a significant challenge in the prevention and management of diseases, with marginalized populations often facing the highest risks and barriers to accessing preventive care. This paper explores the roles of nurses, social workers, and epidemiology inspectors in addressing these inequities within disease prevention programs. By collaborating and integrating their expertise, these professionals can improve access to care, reduce disparities, and promote health equity. The manuscript examines the distinct and overlapping roles of each profession in disease prevention, identifies key barriers to equity, and offers strategies for a more coordinated approach to addressing healthcare disparities.